2024
DOI: 10.1111/eva.13680
|View full text |Cite
|
Sign up to set email alerts
|

Efficient species identification for Pacific salmon genetic monitoring programs

Zachary L. Robinson,
Jeff Stephenson,
Kim Vertacnik
et al.

Abstract: Genetic monitoring of Pacific salmon in the Columbia River basin provides crucial information to fisheries managers that is otherwise challenging to obtain using traditional methods. Monitoring programs such as genetic stock identification (GSI) and parentage‐based tagging (PBT) involve genotyping tens of thousands of individuals annually. Although rare, these large sample collections inevitably include misidentified species, which exhibit low genotyping success on species‐specific Genotyping‐in‐Thousands by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…The study underscores the importance of considering system-specific sampling designs and provides valuable insights into addressing key assumptions and biases associated with tGMR applications. Robinson et al (2024) focused on improving the misidentification of salmonid species in large-scale genotyping efforts. To address this, the study identified 19 primer pairs with 51 species-informative variants, facilitating discrimination among 11 salmonid species, including two Cutthroat Trout subspecies.…”
Section: Mixed-stock Analyses and Parentage-based Taggingmentioning
confidence: 99%
See 1 more Smart Citation
“…The study underscores the importance of considering system-specific sampling designs and provides valuable insights into addressing key assumptions and biases associated with tGMR applications. Robinson et al (2024) focused on improving the misidentification of salmonid species in large-scale genotyping efforts. To address this, the study identified 19 primer pairs with 51 species-informative variants, facilitating discrimination among 11 salmonid species, including two Cutthroat Trout subspecies.…”
Section: Mixed-stock Analyses and Parentage-based Taggingmentioning
confidence: 99%
“…Robinson et al. ( 2024 ) focused on improving the misidentification of salmonid species in large‐scale genotyping efforts. To address this, the study identified 19 primer pairs with 51 species‐informative variants, facilitating discrimination among 11 salmonid species, including two Cutthroat Trout subspecies.…”
Section: Synopsis Of Articles—advances In Salmonid Geneticsmentioning
confidence: 99%